Thyroid function disorders and cardiovascular system (Клиническая и экспериментальная тиреоидология, 2010)
The effects of hyperthyroidism and hypothyroidism on cardiovascular system and cardiovascular events mortality risk is reviewed in this article. Also the problems of levothyroxine replacement in hypothyroid patient with cardiovascular diseases are discussed.